The role of assertiveness and self-esteem in enhancing resilience of rehabilitated adolescents drug addict - Sulistiawati, Surya; Razak, Ahmad; Alwi, Ahkam (Jurnal Psikologi Terapan dan Pendidikan, 2024)
The rapid increase in adolescent drug abuse in Indonesia requires special attention to adolescent resilience against drug abuse and personal factors, such as assertiveness and self-esteem. This study aimed to investigate the role of assertiveness and self-esteem in enhancing resilience among rehabilitated adolescent drug addicts. This study employed a non-experimental quantitative approach with a correlational design. The research sample consisted of 80 individuals selected using a total sampling technique. The instruments used included the Irish Assertiveness Scale, Coppersmith Self-Esteem Inventory, and Grotberg Resilience Scale. Data analysis techniques involved descriptive statistical analysis and multiple regression analysis using SPSS software version 25. The results indicated that assertiveness significantly role the resilience of adolescent drug rehabilitation (r=0.567, p<0.05), while self-esteem also affected resilience (r=0.471, p<0.05). Furthermore, assertiveness and self-esteem jointly played a significant role in the resilience of adolescent drug rehabilitation, with an R Square value of 0.487 (p<0.05). These findings suggest that assertiveness and self-esteem can serve as strong predictors of resilience among adolescent drug addicts.  Rehabilitation programs should focus on assertiveness and social skills education, as well as on developing more effective drug rehabilitation policies.